Modelo de optimización para los sistemas de producción agropecuarios de la microrregión Valle del Cesar, Colombia - Duarte Torres, O.A.; Pulido Herrera, J.I.; Silva Zalzuk, J; Holmann, Federico J. (2003)
Colombia is going through a dynamic research and technology transfer effort in order to improve its livestock enterprise. Animal production system of twenty-two ecoregions in the lowland tropics are being characterized for ex-ante analysis to define technological alternatives. The Valley of Cesar in northern Colombia is a micro-region where agriculture has been its traditional production system, but now, 80% of the land has pastures. This Valley was taken as a case study and we use an optimization model to evaluate its major agricultural crops: rice, cotton, sorghum and also, livestock productions systems: dual-purpose and beef. Additionally, was evaluated the feasibility of applying new and improved technologies, The evaluation of the dual-purpose system included the introduction of Leucaena leucocephala as a protein bank of Angleton pastures and of mixed pastures like Angleton with Clitoria ternatea. Changes in calving and mortality rates were also evaluated by the model. By the other hand, the analysis of crop sensitivity included reduction of production costs and increments in productivity, in order to establish the competitivity level of these systems, faced to dual purpose cattle productions. The results indicate that this is the most profitable system of the major agricultural products for the Valley of Cesar under current productivity levels, input costs, and sale prices. Improvement of Angleton through establishment of Clitoria ternatea associations for dual purpose systems would result in an increment of 194% in annual net income. On the other hand, the annual net income of the system can be increased. The optimization model is a management tool that contributes to identify the activities showing the best potential to get higher economic profit, as well as to determine new technologies that offer better possibilities for production and adoption.